Cladistic analysis of Aradidae (Insecta, Heteroptera) based on morphological and molecular characters. (28th November 2015) - Marchal, Lorène; Guilbert, Eric
Abstract : In this study, we present for the first time a cladistic analysis of the subfamilies of Aradidae, using molecular and morphological characters. Eighty‐three taxa, including 79 species representing eight subfamilies, are treated. The analyses were performed using 72 morphological characters and approximately 1650 bp corresponding to three molecular loci (CO1, 16S and 28S). Characters were analysed using parsimony and Bayesian methods. Based on the combined analyses, we find support for the monophyly of Aradidae, including the subfamilies Aradinae, Aneurinae, Calisiinae, Isoderminae, and Mezirinae and the paraphyly of Prosympiestinae and Chinamyersiinae. In all analyses, Prosympiestinae includes Isoderminae. The Termitaphididae were not found sister to the Aradidae in the Aradoidea.